IMPLEMENTASI SISTEM MONITORING PRODUKSI ENERGI PLTS BERBASIS PROTOKOL MODBUS RTU DAN MODBUS TCP - Widodo Pudji Muljanto; Fransiscus Xaverius Ariwibisono (FKOM UNIKU, 2023)
The use of renewable energy sources is currently starting to grow rapidly in line with the need for environmentally friendly power sources. Solar power plants are a choice of solutions for the community, especially those in areas that have not been reached by the electricity grid. The production of the resulting electrical energy is highly dependent on the capacity of the installed solar panels. In order to monitor solar power plants electricity production and usage load, a facility is needed that can provide real-time information. Besides that, it can easily be accessed remotely by utilizing a network that uses the TCP/IP protocol. The problem that arises then is that the sensor data obtained from the readings must comply with the standard parameters that apply to all sensor equipment. The Modbus RTU and Modbus TCP protocols are the right choice to answer this problem. This research will discuss the implementation of the Modbus RTU/TCP protocol within the scope of solar power plants. Thus, solar power plants electrical energy monitoring system allows it to be applied to networks that are located far from the control or monitoring center.